New data on the distribution and ecology of Lignyoptera fumidaria (Hübner, 1825) in the steppe zone of Northern Kazakhstan - Ivan A. Zuban (Acta Biologica Sibirica, 2026)
New data on the distribution and biology of Lignyoptera fumidaria (Hübner, 1825) in the steppe zone of Northern Kazakhstan is presented. As a result of surveys conducted in October 2025, two new localities of the species were identified in the Aiyrtau District, located 300 km south of previously published records within the region. A mass aggregation of approximately 250 males was recorded within an area of about 3 ha. Adult activity was observed under persistently sub-zero temperatures (down to −6 °C). The new findings significantly expand the current knowledge of the species’ range in Western Siberia and Kazakhstan and highlight its potentially underestimated distribution within the steppe zone.